A Near-Deterministic Mutational Hotspot in Pseudomonas fluorescens Is Constructed by Multiple Interacting Genomic Features. (16th June 2022) - Shepherd, M J; Horton, J S; Taylor, T B
Abstract: Mutation—whilst stochastic—is frequently biased toward certain loci. When combined with selection, this results in highly repeatable and predictable evolutionary outcomes. Immotile variants of the bacterium Pseudomonas fluorescens (SBW25) possess a "mutational hotspot" that facilitates repeated occurrences of an identical de novo single nucleotide polymorphism when re-evolving motility, where ≥95% independent lines fix the mutation ntrB A289C. Identifying hotspots of similar potency in other genes and genomic backgrounds would prove valuable for predictive evolutionary models but to do so we must understand the genomic features that enable such a hotspot to form. Here, we reveal that genomic location, local nucleotide sequence, gene strandedness, and presence of mismatch repair proteins operate in combination to facilitate the formation of this mutational hotspot. Our study therefore provides a framework for utilizing genomic features to predict and identify hotspot positions capable of enforcing near-deterministic evolution.